C is for curious / 2 if for dancing : an A B C of feelings / a 1 2 3 of actions - Hubbard, Woodleigh (San Francisco : Chronicle Books, 1990)
Presents an alphabet of emotions, from angry to zealous./A counting book introducing different types of actions, from one unicorn dreaming to ten dogs riding a bicycle.
Keywords: Emotions - Juvenile literature; Alphabet - Juvenile literature; Counting; Animals - Fiction